Improving the quality of architectural learning outcomes in Iraq - Ibrahim Jawad Kadhim; Falah Khalaf Ali; Ahmed Talib Hameed Haddad (Iraqi Journal of Architecture and Planning, 2017)
The research is concerned with the development of the quality of the learning outcomes through the development of a general system and a road map in order to make a qualitative leap in these outputs. This requires knowledge of the nature of the contemporary global intellectual climate (the climate of globalization) In the developed world. If specialized architectural knowledge is one of this economic knowledge, the graduates of this specialization are a feature of that knowledge that characterizes the country and carry cultural characteristics in addition to the qualities of their architectural specialization in order to practice their profession and provide the local labor market and then the world with their skills and expertise of the quality of excellence Scientifically and practically. This requires the knowledge of the nature of educational thought with its different philosophies and theories, which contribute effectively to the creation of an environment of architectural learning and the formation of those skills and specialized architectural expertise, and then to identify the quality features in architectural education, which is an integral part of the quality of higher education. The problem of research was to determine the quality requirements of the architectural learning outcomes in Iraq within a temporal space compatible with the contemporary intellectual climate, assuming a comprehensive strategic system for the different intellectual contexts affecting the architectural education under one intellectual umbrella to achieve the objective of research in building the ground for the development of architectural education. Which outlines the requirements for the quality of these outputs, and this is what the research done specifically through the development of a general framework for it. To come up with a set of conclusions and recommendations that emphasize the importance of taking into account the impact of global thought and educational thought and the conditions and standards of quality of architectural education by placing them within one system of development that takes into account the conditions of specialization and local culture and market needs.